Validation of the Functional Assessment of Chronic Illness Therapy-Spiritual Well-Being-Expanded (FACIT-Sp-Ex) Across English and Spanish-Speaking Hispanics/Latinos: Results From the Hispanic Community Health Study/Study of Latinos Sociocultural Ancillary Study - Brintz, Carrie E. (Psycholog Relig Spiritual, 2016)
The validity of the Functional Assessment of Chronic Illness Therapy-Spiritual Well-Being (FACIT-Sp) has been examined in primarily non-Hispanics/Latinos with chronic illness. This study assessed the psychometric properties of the non-illness, expanded FACIT-Sp (FACIT-Sp-Ex) in 5,163 U.S. Hispanic/Latino adults. Measures were interviewer-administered in English or Spanish. Confirmatory factor analyses indicated four factors: Meaning, Peace, Faith, and Relational. The scale demonstrated measurement invariance across English and Spanish. Subscales displayed adequate internal and test-retest reliability. Scores were positively associated with Duke Religion Index (DUREL) subscales. When all subscales were entered in a single model, Meaning and Peace were inversely associated with depressive symptoms and positively associated with HRQOL. Faith was positively associated with depressive symptoms and inversely associated with HRQOL. Relational was not associated with any outcome. FACIT-Sp-Ex subscales were generally more strongly associated than DUREL subscales with well-being. The FACIT-Sp-Ex appears to be a valid measure of spiritual well-being in U.S. Hispanics/Latinos.